Depth-profiling of Yb3+ sensitizer ions in NaYF4 upconversion nanoparticles. Issue 23 (2nd June 2017) - Xu, Xiaoxue; Clarke, Christian; Ma, Chenshuo; Casillas, Gilberto; Das, Minakshi; Guan, Ming; Liu, Deming; Wang, Li; Tadich, Anton; Du, Yi; Ton-That, Cuong; Jin, Dayong
Abstract : The non-uniform distribution of Yb 3+ within UCNPs is unraveled and the distribution trends are consistent regardless of the UNCP size or Yb 3+ concentration. Abstract : Enhancing the efficiency of upconversion nanoparticles (UCNPs) and therefore their brightness is the critical goal for this emerging material to meet growing demands in many potential applications including sensing, imaging, solar energy conversion and photonics. The distribution of the photon sensitizer and activator ions that form a network of energy transfer systems within each single UCNP is vital for understanding and optimizing their optical properties. Here we employ synchrotron-based X-ray Photoelectron Spectroscopy (XPS) to characterize the depth distribution of Yb 3+ sensitizer ions in host NaYF4 nanoparticles and systematically correlate the structure with the optical properties for a range of UCNPs with different sizes and doping concentrations. We find a radial gradient distribution of Yb 3+ from the core to the surface of the NaYF4 nanoparticles, regardless of their size or the sensitizer's concentration. Energy dispersive X-ray Spectroscopy (EDX) was also used to further confirm the distribution of the sensitizer ions in the host matrix. These results have profound implications for the upconversion optical property variations.